Implementation of the Teams Games Tournament Model to Increase Student Learning Motivation in Science Learning at MIN 1 Nagan Raya - Nurhalimah; Nurlisna (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to increase students’ learning motivation in science learning through the implementation of the Teams Games Tournament (TGT) cooperative learning model at MIN 1 Nagan Raya. The research employed a Classroom Action Research (CAR) design consisting of two cycles, each including the stages of planning, action, observation, and reflection. The participants were 28 fifth-grade students. Data were collected through learning motivation observation sheets, student motivation questionnaires, interviews, and documentation. The indicators of motivation included students’ attention, participation, persistence, enthusiasm, and learning responsibility during science learning activities. Data analysis was conducted using descriptive quantitative and qualitative techniques by comparing the results of motivation scores across cycles. The findings show that the application of the TGT model significantly improved students’ learning motivation. In the pre-cycle, the average motivation score was 61.42% (low category). After implementing TGT in Cycle I, the motivation score increased to 74.18% (moderate category), indicating a positive change in student engagement and participation. Furthermore, in Cycle II, the motivation score reached 87.36% (high category), demonstrating strong enthusiasm, active collaboration, and greater responsibility in completing science learning tasks. Questionnaire results also confirmed this improvement, with the average student motivation response increasing from 63.10% in Cycle I to 88.20% in Cycle II. The study concludes that the Teams Games Tournament model is effective in fostering a more enjoyable, competitive, and cooperative learning atmosphere, which positively influences students’ motivation in science learning. Therefore, TGT is recommended as an alternative learning strategy to enhance student motivation and classroom learning quality in Islamic elementary schools.